Proposed Indonesian art criticism’s model:old Balinese painting as a case study - Iwan Zahar (2011)
Using western art’s criticism model for Indonesian arts cannot be applicable to all Indonesian arts especially old Indonesian paintings. Feldman’s art criticism model is very popular among the art teachers in USA. Most of art lecturers were familiar with Feldman’s art criticism model because its simplicity which only four phases; describe, analyze, interpret, and judge. Prater proposed a few modifications to Feldman’s formalist model that make it easier to used with a wide range of artwork. The format of Prater’s art criticism model could be divided into six steps; prepare to Critique, examine literal qualities, examine Functional Qualities, Examine the Formal Qualities, Examine the Expressive Qualities, Determine Relevant Theories. Elements and principal design will be different for Old Balinese paintings. Also Prater’s and Feldman’s art’s criticism models did not involve the original context and external context of old Balinese paintings such as Hindu’s philosophy, history, style, and storytelling . We proposed three phase model; internal, original and external context. Internal context; description, original context; styles, compare and contrast, and external context: how other interpreters have understood it, where it has been placed in the history of art.